Discrimination, Narratives and Family History: An Experiment with Jordanian Host and Syrian Refugee Children - Kai Barron; Heike Harmgart; Steffen Huck; Sebastian O. Schneider; Matthias Sutter (The Review of Economics and Statistics, 2021)
We measure the prevalence of discrimination between Jordanian host and Syrian refugee children attending school in Jordan. Using a simple sharing experiment, we find only a small degree of out-group discrimination. However, Jordanian children with Palestinian roots do not discriminate at all, suggesting that a family history of refugee status can generate solidarity with new refugees. We also find that parents' narratives about the refugee crisis are correlated with their children's degree of out-group discrimination, particularly among Syrian refugee children, suggesting that discriminatory preferences are being transmitted through parental attitudes.
Keywords: C91; D90; J15; C93; J13; 330; discrimination; refugees; children; narratives; experiment; integration